Concentrated high intensity electric field (CHIEF) system for non-thermal pasteurization of liquid foods: Modeling and simulation of fluid mechanics, electric analysis, and heat transfer. (2nd February 2017) - Peng, Peng; Song, Hao; Zhang, Tingting; Addy, Min; Zhang, Yaning; Cheng, Yanling; Hatzenbeller, Raymond; Zhu, Xindi; Liu, Shiyu; Liu, Yuhuan; Huang, Xiangzhong; Lin, Xiangyang; et al.
Highlights: The study presents an integrated multi-scale model of the CHIEF system. Strong electric field that effectively kills bacteria is generated by low AC power. The CHIEF system pasteurizes liquid food under low temperature conditions (≤60 °C). System optimizations and recommendations are made based on the simulation results. Abstract: This study develops an integrated, multi-scale model of the pilot concentrated high intensity electric field (CHIEF) system using the finite element method (FEM). The CHIEF system is a novel non-thermal pasteurization technology that uses medium to low voltage (≤10 kV) frequency AC (60 Hz) power supply, and offers satisfactory pasteurization results for liquid food such as juice and milk. The model in this study provides accurate predictions for the fluid behavior, electric field distribution and temperature profile and is validated using experimental results. Results from the model shows that the CHIEF system can provide electric field up to 4000 kV/m with a power supply of 10 kV, enabling a 6-log reduction of bacteria kill. Furthermore, recommendations and optimizations are made based on the modeling results, which would benefit for the process scale-up and design.